A Global Perspective on the Sustainable Development of High-Speed Rail Transport - Pisarek-Bartoszewska, Renata; Novikova, Anastasiia (Towards Sustainable Transport in Logistics and International Trade, 2025)
The aim of the chapter is to present the global development of high-speed rail transport from 1964 to 2024, with a particular focus on selected countries and the aspect of sustainable development. The research is based on a comparative analysis of literature, statistical data, and strategic documents. It was determined that high-speed rail transport constitutes an efficient and low-emission form of mobility, competitive with aviation for distances of up to approximately 1,000 kilometers, and is gaining increasing importance in both infrastructure and communications. A limitation of the study is the selective nature of its spatial analysis. The chapter outlines practical implications for transport infrastructure planning and public policy formation, emphasizing environmental and social goals. The social dimension is revealed in the improved accessibility of transport and regional integration. The value of the chapter lies in showcasing high-speed rail as a tool supporting sustainable development and the transformation of transport systems at global, European, and national levels.